A Smart Decision Model for MSME Investments on Islamic Fintech Platforms: Integrating PSI and SWOT Methods - Esa Kurniawan; Imam Fathurahman; Novira Dian Antasari (School of Computing, Telkom University, 2025)
The rapid growth of Islamic financial technology (fintech) has opened new opportunities for micro, small, and medium enterprises (MSMEs) to access capital. However, investment decision-making remains complex due to diverse risk and return profiles. This study aims to develop a smart investment decision model for MSMEs on Islamic fintech platforms by integrating the Preference Selection Index (PSI) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) methods. Primary data were collected from 30 MSMEs engaged in Islamic fintech funding within the Greater Jakarta area and from 116 users of Islamic fintech platforms serving as respondents. The PSI method was applied to rank MSMEs based on five criteria, return on investment, business risk, capital needs, Sharia compliance, and platform reputation. Results show that Business Risk and Sharia Compliance are the most influential factors determining investment eligibility. The SWOT analysis identified strong platform transparency and Sharia adherence as internal strengths, alongside challenges related to repayment flexibility and financial literacy. Integrating PSI and SWOT produced a comprehensive, Sharia-aligned decision-support framework that enhances objectivity, accuracy, and transparency in MSME funding evaluations. The findings offer actionable insights for investors, fintech operators, and policymakers to strengthen ethical, inclusive, and sustainable Islamic digital finance ecosystems.